PROSES PEMBUKTIAN KARTEL DALAM HUKUM PERSAINGAN USAHA DENGAN MENGGUNAKAN ALAT BUKTI TIDAK LANGSUNG (INDIRECT EVIDENCE) - Sunarti Puspita Sari; Rika Lestari; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The proof of cartel case is a very complex stage. High precision and consistency in cartel proofing is required. The use of indirect evidence indirect evidence is necessary when direct evidence can not be obtained to prove the existence of a cartel agreement, in the case of cartels indirect evidence can be economic evidence and communication evidence. In Article 42 of Law Number 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition jo Article 72 paragraph (1) of the Ministerial Regulation Number 1 Year 2010 does not mention any indirect evidence, but in Law Number 5 Year 1999 and Perkom No. 1 of 2010 also does not prohibit the use of indirect evidence in the handling of business competition cases. So it is necessary to know how the mechanism and standard of evidence use indirect evidence in proof of cartel used by KPPU. From several cases of cartels handled by KPPU such as cooking oil cartels, fuel such charge cartel and cement cartel, there are different mechanisms and standards of evidence in using indirect evidence to prove the cartel cases. There are errors and imperfections of proof of cartel especially in projecting, analyzing and processing data. In its considerations, KPPU only relies on indirect evidence evidence to trap business actors often KPPU is mistaken in finding early indicators to identify cartel agreements such as price parallelism KPPU assumes that price parallelism has automatically proven cartel, whereas according to the implementation guideline of Article 11 About Kartel Perkom Number 04 Year 2011 states price pricing is only an early indicator to identify the cartel and does not necessarily prove the cartel. The proof of cartel by KPPU is inconsistent with the standard and evidentiary mechanism set forth in Law Number 5 Year 1999 which explicitly and limitatively states that in assessing whether or not a violation occurs, the Commission Assembly shall use evidence in the form of witness testimony, expert statement, letter and / or Docs, clues and acknowledgments. Indirect evidence is not a perfect proof. Therefore, there is a need for further and more detailed arrangements on the use of evidence of indirect evidence in proof of cartel or other business competition cases. Keywords: Proof - Indirect Evidence-Business Competition